DESIGN OF RAKA DRYER WITH ETC TECHNOLOGY (ELECTRICAL TEMPERATURE CONTROL) - Irfan Malik Hartanto; Agam Seftian Effendi; Aldiansyah Rusminanda; Choirul Hamzah; Irenta Teguh Wahyu Widodo; Agung Prijo Budijono (AIBPM Publisher, 2018)
The Purpose of this study is to provide solution problems in SMEs Village SepandeSidoarjo regency about conventional yeast drying process in the sun that is not necessarily good or bad weather conditions and long drying time. Method This tool method is designed to resemble a house that has 9 shelves in zigzag and transparent acrylic house walls, with hybrid energy system integrated ETC (ElectricalTemperature Control ). this tool is designed with a capacity of 25 kg yeast katul per process. Result, Expected results are to improve and maintain the drying temperature stability (above 40◦C) and food security (Hygienic), designed by semi-automatic system using electric motors and ETC technology as control system so that productivity increases by 25 kg and effectiveness in machining. The findings of this research is that the tool is designed with Hybrid system ie solar energy and LPG gas infrared stove and ETC technology (Electrical TemperatureControl ) as solution of drying time. Keywords: ETC , SMEs ,Drying , Hybrid Energy system